Fluid Structure Interaction Numerical Simulations of Serial Pulmonary Artery Stenoses - Hong, Eric; Mongrain, Rosaire; Bertrand, Olivier F.; rodes-Cabau, Joseph (CMBES Proceedings, 2007)
The focus of this research is to numerically investigate the effects of fluid structure interaction and spatial configuration of serial stenoses on the hemodynamics and wall motion of the pulmonary artery. Collapse and flow choking phenomena were observed by Kobayashi et al. during a pulsatile flow experiment involving a hydrogel stenosis tube model [1]. In a related study, Tang et al. observed that tube geometry is one of the most important factors affecting flow and wall behaviors [2]. The hypothesis of this study is that some 3D configurations of serial pulmonary artery stenoses are more susceptible to collapse under physiological conditions. i.e. they would exacerbate localized collapse and induce flow choking, leading to a near total occlusion of flow to the lung. This recurring state would produce a lethal ventilation-perfusion mismatch.